ARANSEMEN LAGU LANGKISAU UNTUK ENSEMBEL MUSIK SEKOLAH - Romi Yusi Mustika; Esy Maestro; Jagar Lumban Toruan (SENDRATASIK UNP, 2013)
Abstract The music arragement of the Langkisau song for school music ensembles was inspired by (1) the Langkisau song as one of Minang phenomenal pop songs, that tells about people's habit on the hill of Langkisau (Minang people) who like to wander. (2) It demands the students to be able to play the Langkisau song music arrangement in form of a school music ensemble. (3) This arrangements combines traditional musical instruments with western musical instruments which available at school. Kata kunci : Aransemen, Lagu Langkisau, Ensembel, Musik Sekolah.